Queen Esther Saves Her People - Penny Frank; Tony Morris (UK USA Lion Publishing, 1989)
Retells the story of Esther, a Jewish girl who became queen of Persia and influenced the king to make life easier for the Jews in his provinces.
GB8538592 bnb
color illustrations ; GB8928471 bnb Australia
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Bible stories, English -- Esther; Theology